Quantitative assessment of shoreline changes along the tropical West Coast, Maharashtra, India: A remote sensing and GIS approach - Herlekar, Milind A.; Kamble, Prafull B.; Gawali, Praveen B.; Hanamgond, Pramod T.; Aher, Sainath P. (My University, 2023)
Shoreline changes have been monitored for the tropical West Coast of Maharashtra using the Survey of India (SOI) toposheet, Remote Sensing (RS) data, and its incorporation in the Geographical Information System (GIS) for the time period from 1980 to 2013. Indian Remote Sensing (IRS) Resource Sat (P6-R2) satellite data of 2013 year were geocoded using an image-to-image rectiBcation process with the help of permanent points on the ground. The registered satellite imageries were added in Arc GIS 10.3 software with a false colour composite (FCC) band combination (3:2:1) to get clear contrast of the land–water boundary. The toposheet and satellite imagery waterlines were digitised using the line feature in Arc GIS 10.3 software. The shorelines digitised for different years were overlaid, and polygons were created for every changed location to compute shoreline changes from 1980 to 2013 to quantify the rate of erosion or accretion along the shoreline under investigation. Computed results were validated through detailed ground observations. The obtained results indicate that *265 km (45.28%) of the coast is under erosion, *234.17 km (40.02%) under deposition and *85.97 km (14.70%) of the coast is stable. Maximum shoreline erosion is observed in the northern part extent from the Alibag to Shrivardhan and the deposition in the southern part of the coastal tract. The Maharashtra coast lost *1.65 km2 net area during 1980–2013. In some places, sand spits are growing or receding in response to coastal currents and storm events. The present pattern of shoreline changes is related to physical setting of the shoreline, varying wind and wave climate and anthropogenic activity.
Keywords: Shoreline changes; RS-GIS; Erosion–accretion; Maharashtra coast